1996
DOI: 10.1021/la960486q
|View full text |Cite
|
Sign up to set email alerts
|

Langmuir and Langmuir−Blodgett Films of a Phosphorus Derivative

Abstract: We have studied the ability of a novel molecule (diphenyl bis(octadecylamino) phosphonium bromide) to form both Langmuir films and Langmuir−Blodgett films under different experimental conditions. It has been found that this substance is capable of forming stable monolayers at the air−water interface and building up highly ordered LB films yielding Z-type LB films of high quality (transfer ratio of 1) which were characterized by UV−vis and IR spectra, electron microscopy, and X-ray diffraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 40 publications
4
43
0
Order By: Relevance
“…The substrates (glass, CaF 2 , quartz, and Lindemann glass capillaries for the SEM, IR, UV-vis, and X-ray measurements, respectively) were cleaned thoroughly, as was previously described (2,27). The monolayers were transferred onto the substrates by the vertical dipping method.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The substrates (glass, CaF 2 , quartz, and Lindemann glass capillaries for the SEM, IR, UV-vis, and X-ray measurements, respectively) were cleaned thoroughly, as was previously described (2,27). The monolayers were transferred onto the substrates by the vertical dipping method.…”
Section: Methodsmentioning
confidence: 99%
“…In the latter case, the pressure increases again after the plateau and the area per molecule after it is one-half the area just before it begins. This plateau also appears in the isotherms of DPOP + when pure water is used as subphase and a detailed study of this phenomenon (27) concluded that the molecules suffered a rearrangement of the head groups (overshoot) and the formation of a bilayer (plateau). The experiments performed using LiTCNQ in the subphase (values of the area per molecule, hysteresis cycles, and the different slopes of the films absorbance vs numbers of layers transferred before and after the plateau) indicate that we are facing again the same situation as when pure water is used as subphase.…”
Section: Langmuir Filmsmentioning
confidence: 95%
See 3 more Smart Citations